The Difference of Physiological and Proteomic Changes in Maize Leaves Adaptation to Drought, Heat, and Combined Both Stresses - Zhao, Feiyun; Zhang, Dayong; Zhao, Yulong; Wang, Wei; Yang, Hao; Tai, Fuju; Li, Chaohai; Hu, Xiuli (Frontiers in Plant Science, 2016)
At the eight-leaf stage, maize is highly sensitive to stresses such as drought, heat, and their combination, which greatly affect its yield. At present, few studies have analyzed maize response to combined drought and heat stress at the eight-leaf stage. In this study, we measured certain physical parameters of maize at the eight-leaf stage when it was exposed to drought, heat, and their combination. The results showed an increase in the content of H2O2 and malondialdehyde (MDA), and in the enzyme activities of superoxide dismutase (SOD), ascorbate peroxidase (APX), and glutathione reductase (GR), but a decrease in the quantum efficiency of photosystem II (ΦPSII). The most obvious increase or decrease in physical parameters was found under the combined stress condition. Moreover, to identify proteins differentially regulated by the three stress conditions at the eight-leaf stage, total proteins from the maize leaves were identified and quantified using multiplex iTRAQ-based quantitative proteomic and LC-MS/MS methods. In summary, the expression levels of 135, 65, and 201 proteins were significantly changed under the heat, drought and combined stress conditions, respectively. Of the 135, 65, and 201 differentially expressed proteins, 61, 28, and 16 responded exclusively to drought stress, heat stress, and combined stress, respectively. Bioinformatics analysis implied that chaperone proteins and proteases play important roles in the adaptive response of maize to heat stress and combined stress, and that the leaf senescence promoted by ethylene-responsive protein and ripening-related protein may play active roles in maize tolerance to combined drought and heat stress. The signaling pathways related to differentially expressed proteins were obviously different under all three stress conditions. Thus, the functional characterization of these differentially expressed proteins will be helpful for discovering new targets to enhance maize tolerance to stress.